«Woche für Woche neue Preisaufschläge» Nahrungsmittel-, Energie- und Ressourcenkonflikte in der Schweiz des Ersten Weltkrieges - Krämer, Daniel; Pfister, Christian; Segesser, Daniel Marc (Wirtschafts-, Sozial- und Umweltgeschichte, 2016)
The focus of this volume is on economic supply in Switzerland during the First World War. In the second half of the war, especially the shortage of food and energy became a question of national existence. The volume connects different historiographic approaches, combines them in a new way. and pays special attention to the protagonists involved.